Benchmarking Peruvian Banks using Data Envelopment Analysis - Charles, Vincent (2011)
Despite the growing literature on bank efficiency worldwide over the last decade, researchers have neglected the Peruvian banking sector. In this paper, the technique of data envelopment analysis (DEA) is used to investigate the efficiency of Peruvian banks for the period 2000 to 2009 to benchmark currently existing banks based on their super-efficiency scores over time. Further, an in-depth analysis of currently existing banks for the period 2008 to 2009 is conducted to check the robustness of DEA efficiency scores and the potential improvement of inputs and outputs for inefficient banks, indicating by how much and in what areas inefficient banks need to improve in order to be efficient. Our finding shows an increasing trend in technical efficiency during the period 2000 to 2009 which gives an indication of an affirmative effect of the reform process in the Peruvian banking sector. On average, the multinational banks are performing better than are domestic banks throughout the period except in 2007, during which a sharp decline in efficiency performance for both the groups was apparent, possibly a result of global financial turmoil. The application of jackknifing analysis with appropriate statistical tools shows the DEA efficiency scores are robust. Among the 14 currently existing banks, Banco Ripley and Banco Santander Peru were the best performers, whereas Banco Azteca was the worst performer, followed by Interbank and Banco de Comercio. Furthermore our findings suggest that inefficient banks require more rigorous policies with respect to the allocation of funds for additional loans as well as other earnings assets. In this way, presently inefficient banks may approach the efficiencies of the best practice banks.